Porcine Reproductive and Respiratory Syndrome Virus (PRRSV-1) recognition of peptide sequences in CD163 SRCR5 - Williams, Carly; Stoian, Ana M.M.; Rowland, Raymond R.R. (My University, 2019)
PRRSV is an important swine pathogen that uses macrophages as important target cells for viral replication. CD163, a macrophage specific molecule involved in several homeostatic processes, was also identified as a receptor for PRRSV. Research shows that a complete deletion of CD163 SRCR5 can produce pigs that are entirely resistant to infection with PRRSV. Therefore, our goal is to find the smallest mutation in SRCR5 that will prevent PRRSV-1 infection, but also conserve CD163’s biological functions. The CD163 constructs used in this study were previously generated and tested for permissiveness to PRRSV-2 infection. Briefly, each construct carries an insertion of Proline-Arginine dipeptides (PR) at every 30 bp along the SRCR5 cDNA. All of the CD163 constructs were fused to a green fluorescent protein (GFP) which allowed visualization of the proper expression for each recombinant protein on non-permissive HEK293T cells. In order to test the permissiveness of each CD163 SRCR5 construct to PRRSV-1 infection, the cells expressing each mutant were infected with a PRRSV-1 strain, Lelystad. Infection results were visualized by IFA staining using an antibody recognizing PRRSV-N protein. The results showed a wide range of infection rates, from mutation that showed no or little effect to mutations that almost completely blocked infection. For example, insertion of PR in positions 15, 38, 62 and 78 had no effect on infection, whereas insertion of PR in positions 58 and 100 showed great reduction in PRRSV-1 infection. These results show the possible contact regions between the PRRSV viral proteins and the CD163 receptor.
Keywords: Spring 2019